Modern technologies in early detection and differential diagnostics of gastric cancer - A. F. Chernousov; V. V. Levkin; A. V. Egorov; S. S. Kharnas; T. V. Khorobrykh; N. V. Gagarina; N. S. Gorovaya; V. Ya. Zavodnov; V. B. Loshchenov; N. L. Okhotnikova; E. Yu. Patoka; S. K. Ternovoy; et al. (Сеченовский вестник, 2022)
The article deals with the estimation of sensitivity of different diagnostic methods in differential diagnostics of stomach diseases. We found that the performance of the fluorescent diagnostics is very high in the primary diagnosis of gastric cancer and in the differential diagnosis of benign and malignant stomach lesions: sensitivity — 96%, specificity — 78%. The detection rate of gastric cancer with the use of transabdominal ultrasonography reaches 95,6% for the localization of the tumor in antrum or lower third of the stomach body. The diagnostic accuracy is higher in cases of advanced gastric cancer. We also estimate the diagnostic performance of the multidetector computed tomography in the detection and staging of gastric cancer. Multidetector computed tomography with multiplanar reformation and virtual gastroscopy offers new opportunities for imaging of gastric diseases. The detection rate of gastric cancer using this method is 97% regardless of the localization of the tumor. Diagnostic potential of all mentioned methods of visualization of gastric lesions needs to be further explored.